Neuropathic pain depends upon d-serine co-activation of spinal NMDA receptors in rats. (31st August 2015) - Lefèvre, Yan; Amadio, Aurélie; Vincent, Peggy; Descheemaeker, Amélie; Oliet, Stéphane H.R.; Dallel, Radhouane; Voisin, Daniel L.
Highlights: We investigated the role ofd -serine in pain after spinal nerve ligation in rats. Allodynia depended upon gliald -serine that co-activates spinal NMDA receptors. Spinald -serine may be a target to treat mechanical allodynia in neuropathic pain. Abstract: Activation of N -methyl-d -aspartate (NMDA) receptors is critical for hypersensitivity in chronic neuropathic pain. Since astroglia can regulate NMDA receptor activation by releasing the NMDA receptor co-agonistd -serine, we investigated the role of NMDA receptor andd -serine in neuropathic chronic pain. Male Wistar rats underwent right L5–L6 spinal nerve ligation or sham surgery and were tested for mechanical allodynia and hyperalgesia after 14 days. Acute intrathecal administration of the NMDA receptor antagonistd -AP5 as well as chronic administration of the glia metabolism inhibitor fluoroacetate significantly reduced mechanical allodynia in neuropathic rats. The effect of fluoroacetate was reversed by acutely administered intrathecald -serine. Degradingd -serine using acute intrathecal administration ofd -aminoacid oxidase also reduced pain symptoms. Immunocytochemistry showed that about 70% of serine racemase, the synthesizing enzyme ofd -serine, was expressed in astrocyte processes in the superficial laminae of L5 dorsal horn. Serine racemase expression was upregulated in astrocyte processes in neuropathic rats compared to sham rats. These results show that neuropathic pain depends upon gliald -serine that co-activates spinal NMDA receptors.